Etiology and clinical characteristics of acute viral hepatitis in South Korea during 2020–2021: a prospective multicenter study - Chan Young Jeong; Gwang Hyeon Choi; Eun Sun Jang; Young Seok Kim; Youn-Jae Lee; In Hee Kim; Sung Bum Cho; Jae Hyun Yoon; Kyung-Ah Kim; Dae Hee Choi; Woo Jin Chung; Hyun Chin Cho; et al. (Scientific Reports)
Abstract This prospective, 12-center study investigated the etiology and clinical characteristics of acute viral hepatitis (AVH) during 2020–2021 in South Korea, and the performance of different diagnostic methods for hepatitis E virus (HEV). We enrolled 428 patients with acute hepatitis, of whom 160 (37.4%) were diagnosed with AVH according to predefined serologic criteria. The clinical data and risk factors for AVH were analyzed. For hepatitis E patients, anti-HEV IgM and IgG were tested with two commercial ELISA kits (Abia and Wantai) with HEV-RNA real-time RT-PCR. HAV, HEV, HBV, HCV, Epstein-Barr virus (EBV), cytomegalovirus, and herpes simplex virus accounted for AVH in 78.8% (n = 126), 7.5% (n = 12), 3.1% (n = 5), 1.9% (n = 3), 6.9% (n = 11), 1.2% (n = 2), and 0.6% (n = 1) of 160 patients (median age, 43 years; men, 52.5%; median ALT, 2144 IU/L), respectively. Hospitalization, hemodialysis, and intensive care unit admission were required in 137 (86.7%), 5 (3.2%), and 1 (0.6%) patient, respectively. Two patients developed acute liver failure (1.3%), albeit without mortality or liver transplantation. Ingestion of uncooked clams/oysters and wild boars’ blood/bile was reported in 40.5% and 16.7% of patients with HAV and HEV, respectively. The concordance rate between the anti-HEV-IgM results of both ELISA kits was 50%. HEV RNA was detected in only 17% of patients with HEV. The diagnosis of HEV needs clinical consideration due to incomplete HEV diagnostics.